2012
DOI: 10.21726/rsbo.v8i4.1085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of canal transportation and centering ability of hand Protaper files and rotary Protaper files by using micro computed tomography

Abstract: Introduction and objective: The aim of the present study was to compare root canal preparation with rotary ProTaper files and hand ProTaper files to find a better instrumentation technique for maintaining root canal geometry with the aid of computed tomography. Material and methods: Twenty curved root canals with at least 10 degree of curvature were divided into 2 groups of 10 teeth each. In group I the canals were prepared with hand ProTaper files and in group II the canals were prepared with rotary ProTaper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Regarding the centering ability and transportation, ProTaper rotary system recorded highest mean value of canal transportation and least centric ability when compared with the other tested rotary instruments. This was in agreement with previous studies (8,9,25) .These findings could be attributed to the sharp cutting edges of the convex triangular cross sectional design and the multiple tapers along the cutting surface of the files compared with the constant taper embraced by the other tested instruments used. In addition, the apical enlargement performed until F3 for standardization might have an impact on the results because NiTi files with tapers greater than 0.04 were previously suggested not be used for apical enlargement of curved canals or else transportation would result (9) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the centering ability and transportation, ProTaper rotary system recorded highest mean value of canal transportation and least centric ability when compared with the other tested rotary instruments. This was in agreement with previous studies (8,9,25) .These findings could be attributed to the sharp cutting edges of the convex triangular cross sectional design and the multiple tapers along the cutting surface of the files compared with the constant taper embraced by the other tested instruments used. In addition, the apical enlargement performed until F3 for standardization might have an impact on the results because NiTi files with tapers greater than 0.04 were previously suggested not be used for apical enlargement of curved canals or else transportation would result (9) .…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that, ProTaper rotary files maintaining the original canal curvature than ProTaper hand files, where they produced lesser transportation and remained better centered in the canal (7) . On the Other hand, it has been reported that ProTaper tended to transport towards the outer aspect of the curve compared to RaCe instruments (8) .…”
Section: Introductionmentioning
confidence: 92%